GLYCERINIZATION OF FOLIAGES FOR DRY FLOWER PRODUCTS MAKING - K. VISHNUPRIYA,; M. JAWAHARLAL, (The Bioscan, 2014)
The study was undertaken to assess the effect of glycerine on preservation of foliages for making dry flower products. The experiment was conducted with four different foliages viz., podocarpus, leather leaf fern, baby eucalyptus and silver dollar and two methods of glycerinization (full dip, uptake) with different concentrations of glycerine (10, 20, 30, 40 and 50%). Uptake method of drying with 10% glycerine reduced the time taken for drying of podocarpus and full dip method of glycerine at 10% concentration recorded the lowest moisture loss of 5.24% in podocarpus as compared to other foliages. Among the different drying treatments, full dip method of glycerine at 50% improved all the quality parameters for podocarpus and uptake method of glycerine at 10% improved all the quality parameters for leather leaf fern, baby eucalyptus and silver dollar respectively.